TACROLIMUS DRUG LEVEL AND RESPONSE TO TREATMENT IN IDIOPATHIC CHILDHOOD STEROID RESISTANT NEPHROTIC SYNDROME - Shah, Syed Sajid Hussain; Hafeez, Farkhanda; Akhtar, Naureen (Journal of Ayub Medical College Abbottabad, 2015)
Background: The management of Steroid Resistant Nephrotic Syndrome (SRNS) is an uphill task for paediatric nephrologists as immunosuppressive agents are the mainstay of treatment in these patients. Tacrolimus is used along with steroids. This study is conducted to see the relationship between the tacrolimus dose, drug level and response in the management of SRNS. Methods: This quasi experimental study was conducted at The Children's Hospital Lahore over a period of one year. Patients with SRNS of either sex and 1-10years of age were included and those with secondary nephrotic syndrome were excluded. Tacrolimus was given at a dose of 0.05-0.1 mg/kg/day in 2 divided doses along with steroids. The follow-up was done for six months with proteinuria monitoring and tacrolimus drug levels done two weeks after initiation of treatment. Results: Out of 42 patients, 27 (64.3%) were males and 15 (35.7%) were females. The most common histological diagnosis observed was mesangio-proliferative glomerulonephritis in 30 (71.4%) patients. The tacrolimus trough level range was 0.5-15.20 ng/ml with a mean value of 4.68 ng/ml±2.85. Forty-one (97.6%) children showed complete response to treatment while one patient showed partial response. Conclusion: This study suggests that tacrolimus is an effective drug for treatment of SRNS in paediatric patients and there is no linear relationship between the drug dose, response and drug level.